2008
DOI: 10.1007/s10694-008-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural-network Based Predictive Model for Pre-evacuation Human Response in Domestic Building Fire

Abstract: that occupants took 1-3 h to leave the 110-storey buildings, and the pre-movement reactions could account for over twothirds of the overall evacuation time. This indicates that a thorough understanding of the pre-evacuation behavioral response of people under fire situations is of prime importance to fire safety design in buildings, especially for complex and ultra highrise buildings. In view of the stochastic (the positions of the occupants) and fuzzy (uncertainty) nature of human behavior (Fraser-Mitchell, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…An Adaptive Network based Fuzzy Inference System (ANFIS) has been proposed by Lo et al [2009] to predict the pre-evacuation behaviour of evacuees based on back propagation oriented learning procedures. The authors have modelled their proposed soft computing approach by training the network with data acquired from structured human behaviour.…”
Section: Overview Of Evacuation Models Using Artificial Neural Networkmentioning
confidence: 99%
“…An Adaptive Network based Fuzzy Inference System (ANFIS) has been proposed by Lo et al [2009] to predict the pre-evacuation behaviour of evacuees based on back propagation oriented learning procedures. The authors have modelled their proposed soft computing approach by training the network with data acquired from structured human behaviour.…”
Section: Overview Of Evacuation Models Using Artificial Neural Networkmentioning
confidence: 99%
“…Over the last few decades, considerable research has focused on evacuation behavior analysis related to hurricane evacuation [1][2][3][4][5][6] and building fire evacuation [7,8]. The majority of existing studies focused on individual and household evacuation decision-making and behavioral responses.…”
Section: Introductionmentioning
confidence: 99%
“…By far, several methods have been put forward for helping us understand evacuation decision-making, including contingency table analysis [8], artificial neural network [7], and logistic regression analysis [4,6,9,10]. Among the above methods, contingency table analysis is only used to determine whether dependence exists between evacuation decision-making and related factors for a given significant level.…”
Section: Introductionmentioning
confidence: 99%
“…His exemplified case study showed that the reliable evaluation result could be obtained in shorter time as long as the values of related fire risk evaluation indexes are input into the model. Lo et al [6] proposed an Adaptive Network Fuzzy Inference System based algorithm to predict the pre-movement reaction of people in fire. Their training results showed that such an approach can be applied in manipulating the limited data of human reaction in fire and can serve as part of an evacuation model to predict the initial response of the evacuees.…”
Section: Introductionmentioning
confidence: 99%